Development of microchip isoelectric focusing and scanning laser induced fluorescence detection for simultaneous enzyme activity - Jia, Shu (Kansas State University, 2021)
Matrix Metalloproteinases (MMPs) are a group of extracellular matrix proteinases expressed in normal and pathological processes, such as immune response and carcinogenesis. Dysregulation of MMP activities is commonly found in multiple pathways in cancer development, including degradation of extracellular matrix, reduction of cell-cell/cell-matrix adhesion, and facilitation of tumor cells metastatic migration. Quantification of MMP activities has been utilized in cancer early detection, cancer staging, and immunotherapies. Currently, the ability to measure MMP activities with an affordable point of care device is still lacking. This project aims at addressing the need by developing a microfluidic isoelectric focusing device with modified magnetic nanoparticles to measure MMP activities in blood serum samples. Microfluidic isoelectric focusing devices were developed to separate fluorescently labeled peptide substrates based on isoelectric point difference. Sample handling, sample treatment, analyte separation, and fluorescence detection were integrated into the microfluidic IEF device. Magnetic nanoparticles with MMP substrates were digested by MMPs in the sample to cleave peptides. MMP activities were quantified by the ratio of cleaved and uncleaved substrates. This thesis/presentation will review the development of the novel automated microfluidic IEF device and its application in enzyme activity assays.
Keywords: Isoelectric focusing; Matrix Metalloproteinase; Microfluidic; Cancer early detection